Between Dictatorship and Democracy : Russian Post-Communist Political Reform - McFaul, Michael, 1963-; Ri︠a︡bov, Andreĭ; Petrov, Nikolaĭ (Nikolaĭ Vladimirovich) (Book collections on Project MUSE., 2004)
For hundreds of years, dictators have ruled Russia. Do they still' In the late 1980s, Soviet President Mikhail Gorbachev launched a series of political reforms that eventually allowed for competitive elections, the emergence of an independent press, the formation of political parties, and the sprouting of civil society. After the collapse of the Soviet Union in 1991, these proto-democratic institutions endured in an independent Russia. But did the processes unleashed by Gorbachev and continued under Russian President Boris Yeltsin lead eventually to liberal democracy in Russia' If not, what kind of political regime did take hold in post-Soviet Russia' And how has Vladimir Putin's rise to power influenced the course of democratic consolidation or the lack thereof' Between Dictatorship and Democracy seeks to give a comprehensive answer to these fundamental questions about the nature of Russian politics.